Sobre la perífrasis 'soler' + estativo: una lectura genérica - Vatrican, Axelle (Borealis – An International Journal of Hispanic Linguistics, 2015)
Abstract. This paper presents a semantic analysis of a periphrastic construction which has not been studied at this time in Spanish: soler + stative (Un poeta suele ser un hombre normal, “A poet usually is a normal man”). Whereas the habitual construction has been largely studied (Juan suele cantar “Juan usually sings”), it seems that the first one does not carry the same interpretation. We will claim that we need to distinguish between two readings: the habitual reading on the one hand and the generic reading on the other hand. According to Menéndez-Benito (2013), Krifka et al. (1995) and Shubert & Pelletier (1989), among others, we will argue that soler contains a frequentative adverb of quantification Q. In the habitual reading, the Q adverb quantifies over an individual participating in an event at a time t (Juan está cantando, “Juan is singing”), whereas in the generic reading, Q adverb quantifies over a characterizing predicate (un poeta es un hombre normal, “A poet is a normal man”). In the habitual reading, the NP must refer to an individual and the VP to a dynamic event anchored in space and time. In the generic reading, the NP must refer to a class of objects and the VP to a stative predicate.